2002
DOI: 10.1007/s11920-002-0073-y
|View full text |Cite
|
Sign up to set email alerts
|

The roots of depression in adolescent girls: Is menarche the key?

Abstract: Before adolescence, the rates of depression are similar in girls and boys (or are slightly higher in boys). Yet with the onset of puberty, the gender proportion of depression dramatically shifts to a two girls to one boy ratio. What, then, is the relationship between menarche and the onset of major depression in early adolescence? Recent literature intimates that vulnerability to depression may be rooted in an intricate meld of genetic traits, normal female hormonal maturational processes, and gender socializa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 148 publications
(138 reference statements)
2
28
1
1
Order By: Relevance
“…21 Depression rate shifted from slightly higher in prepubescent boys to a twofold higher in girls coinciding with the onset of menarche. 32 As such, depression and other comorbid psychiatric or psychosocial conditions could potentially be a contributing factor to poorer sleep in adolescent girls reported in this study. Finally, another study of New Jersey adolescents showed that females practiced more instant messaging than their male schoolmates during the night and that texting after lights out contributed to impaired sleep quantity and quality relative to males.…”
Section: Ming Et Almentioning
confidence: 75%
“…21 Depression rate shifted from slightly higher in prepubescent boys to a twofold higher in girls coinciding with the onset of menarche. 32 As such, depression and other comorbid psychiatric or psychosocial conditions could potentially be a contributing factor to poorer sleep in adolescent girls reported in this study. Finally, another study of New Jersey adolescents showed that females practiced more instant messaging than their male schoolmates during the night and that texting after lights out contributed to impaired sleep quantity and quality relative to males.…”
Section: Ming Et Almentioning
confidence: 75%
“…These disorders are more common in women than in men, and some evidence indicates that estrogen may contribute to this discrepancy. Specifically, the higher prevalence of depression in women first arises at puberty 33,34 , maintains through the child-bearing years, and then declines, such that it is equally likely to occur in postmenopausal women as in men of the same age. 35 Furthermore, administration of estrogen can exacerbate depressive symptoms in young women 36 , but not in menopausal women.…”
Section: Clinical Relevancementioning
confidence: 99%
“…Women suffer from major depression and anxiety disorders at rates significantly higher than men (Sloan and Kornstein, 2003). Moreover, the occurrence of depression and anxiety-based pathologies increases significantly after puberty in women, and the incidence is highest during a woman's reproductive years, suggesting that ovarian hormones are involved in the etiology of these pathologies (Palanza, 2001;Born et al, 2002). Studies in rodents also indicate gender differences in emotional behavior.…”
Section: Introductionmentioning
confidence: 99%